1993
DOI: 10.1002/jcla.1860070102
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings on the variation of serum apolipoprotein levels in neural degenerative disorders

Abstract: We measured six apolipoproteins (AI, AII, B, CII, CIII, and E) in the serum of patients with several kinds of neural diseases [diabetic neuropathy and neural degenerative disorders (motor neuron degenerative disorders, spinocerebellar degeneration, Parkinson's disease)], comparing them to the age-matched healthy controls using the immunoturbidimetric method. Statistically significant decreases of serum apo-AI, apo-A-II and increases of apo-CIII, apo-E were observed in neural degenerative diseases; and, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Although the differences were less significant than those observed for apoD, apoE levels were also significantly higher in the CSF of AD patients (p < 0.001) and in patients with other neuropathologies (p < 0.05) than in the CSF of control subjects. In other studies, apoE concentrations in the CSF of AD subjects have been reported to be higher (Carlsson et al, 1991;Ikeda et al, 1993), comparable (Pirttila et al, 1994), or lower (Blennow et al, 1994;Lehtimaki et al, 1995) than those of control subjects. Increased CSF apoE levels have been reported in several other neuropathologies, including Creutzfeld-Jakob disease (Namba et al, 1991;Amouyel et al, 1994), scrapie disease (Diedrich et al, 1991), and Lewy body disease (St.-Clair et al, 1994).…”
Section: Discussionmentioning
confidence: 79%
“…Although the differences were less significant than those observed for apoD, apoE levels were also significantly higher in the CSF of AD patients (p < 0.001) and in patients with other neuropathologies (p < 0.05) than in the CSF of control subjects. In other studies, apoE concentrations in the CSF of AD subjects have been reported to be higher (Carlsson et al, 1991;Ikeda et al, 1993), comparable (Pirttila et al, 1994), or lower (Blennow et al, 1994;Lehtimaki et al, 1995) than those of control subjects. Increased CSF apoE levels have been reported in several other neuropathologies, including Creutzfeld-Jakob disease (Namba et al, 1991;Amouyel et al, 1994), scrapie disease (Diedrich et al, 1991), and Lewy body disease (St.-Clair et al, 1994).…”
Section: Discussionmentioning
confidence: 79%
“…A number of proteins did not show clear directions in their associations with the various conditions with the results of different studies contradicting each other. For example, apolipoprotein E was found to be elevated in PD by Ikeda et al [65], but lowered in Alberio et al [52] and Goldknopf et al [56]. This could be due to small sample sizes, cohort heterogeneity and differences in proteomic approaches, and will need further validation.…”
Section: Discussionmentioning
confidence: 93%
“…(−) Alberio et al [52] (−) Dean et al [51] (−) Soares et al [18] (−) Goldknopf et al [56] (−) Doecke et al [17] (+) Ikeda et al [65] (−) Hu et al [19] (−) Zhang et al [21] With Brain Amyloid: (−) Kiddle et al [20] (+) Thambisetty et al [27] With treatment response: (+) Akuffo et al [23] Alpha-2-macroglobulin (+) Schwarz et al [58] (+) Fujita et al [49] (+) Akuffo et al [23] (−) Domenici et al [60] (+) Tsiouris et al [50] With AD:…”
Section: Ad Candidate Proteins In Other Brain Disordersmentioning
confidence: 99%
“…It is recognized that some apolipoproteins are involved in the process, such as Apo AI, Apo A-II, Apo E. There was evidence found in the literature that significant decreases of serum Apo A-I, Apo A-II and increases of Apo C-III, Apo E were discovered in neural degenerative diseases. 4 There are a large portion of amphipathic a-helices in the protein structure domain of Apolipoproteins. This can maintain the conformational stability without lipid proteins to form the amyloid-like protein deposition, such as aand b-synuclein which also have amphipathic a-helix domains.…”
Section: Discussionmentioning
confidence: 99%